Preparation and Characterization of Ticagrelor Solid Self nano-emulsion (Journal of Pharmaceutical Negative Results, 2022)
Self nano emulsifying drug delivery system (SNEDDS) can be considered as a concentrated emulsion, containing drug that is solubilized in a mixture of oil, surfactant and co-surfactant, They administered as an oily liquid dosage form, and after mixing in the aqueous environments of the stomach they form nano emulsion. Although it is a useful method to improve solubility and bioavailability of many drugs of class II (water insoluble) and class IV ( water insoluble and impermeable) drugs it have disadvantages mainly it is administered as a liquid encapsulated in soft gelatin capsules, which might be sensitive to humidity. Furthermore, the liquid preparation might cause compatibility issues with the shell of the soft gelatin capsule, so this can be avoided by solidifying the preparation to produce solid SNEDDS.Method: After preparation of Ticagrelor a class IV drug as liquid self nano emulsion (SNE), the best solidifying agent chosen according to its loading capacity of liquid formula. Then the prepared solid formula is subjected for further test like studying the micrometric properties, disintegration time, and in-vitro dissolution studies.Result: results showed that Avicel 102, and Aerosil 200 are the best two solidifying agent that carry the liquid formula with less amount of powder,therefore a mixture of different ratios made of these two powders. The best formula that pass all the tests was containing 90% Avicel 102 and 10% Aerosil 200.Conclusion: combining Avicel 102 and Aerosil 200 in ratio (90 to 10) formed a solid formula of the liquid SNE with acceptable micrometric properties and dissolution rate in comparison with the marketed drug of ticagrelor (Brilinta).